Study on the impact of private standards on CARIFORUM countries : final report - McDonell, Ian (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The objectives of this study were “to determine the impact of private industry standards on CARIFORUM countries, specifcally with regard to market access (international and regional), cost of compliance and poverty (alleviation/ creation).” Particular emphasis was to be placed on the impact on smallholders.